Limited Effects of Pain Control Treatments on Behaviour and Weight Gain of Pure and Crossbred Nellore Heifer Calves When Subjected to Hot-Iron Branding - Hernandez, Adalinda; Trindade, Pedro Henrique Esteves [UNESP]; Paranhos Da Costa, Mateus José Rodrigues [UNESP]; Jung, Jens; Berg, Charlotte (MDPI, 2022)
Hot-iron branding is still commonly performed in cattle farming in tropical countries, and possibly has negative consequences for animal welfare and weight gain. This study examined the behavioural and weight gain responses of pure and crossbred Nellore heifer calves subjected to hot-iron branding on the cheek, without and with use of anaesthesia and analgesia. Ninety-two heifer calves, around 120 days old, were studied prospectively when subjected to hot-iron branding on the cheek (a statutory procedure in Brazil following brucellosis vaccination). Four randomly selected groups of calves were allocated to four treatments: no pain control (CO); subcutaneous anaesthetic local block (LA); intramuscular analgesia (meloxicam) (LT); and local anaesthesia plus meloxicam (LL). Behaviour, flight speed and body weight were evaluated before, during, and five (5-d) and 60 days (60-d) after branding. For these parameters, the only difference observed was higher tension in the CO group 5-d post-branding, suggesting a short-term negative effect of branding without pain control. The limited effects of the pain control treatments suggest interference in pain assessment by other factors, such as expression of fear and stress. Despite the lack of differences observed in behaviour and production parameters, facial hot-iron branding is an obvious welfare issue and, due to the additional handling involved, adoption of a simple pain relief protocol is not sufficient to minimise the welfare impact.
Keywords: animal welfare; Bos indicus; cattle; facial expression; pain assessment; qualitative behavioural assessment; weight gain